PENANGANAN SAMPAH RUMAH TANGGA DI KOTA BANDUNG: NILAI TAMBAH DAN POTENSI EKONOMI - Indartik Indartik; Elvida Yosefi Suryandari; Deden Djaenudin; Mirna Aulia Pribadi (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2018)
Increasing waste generation has a negative impact on environmental health and socio-economic aspects. Driving factors of increasing waste generation are population growth, economic activities and  lack of publicawareness.  This study aims to (1) determine waste management policies, (2) evaluate the performance of waste management in Bandung City; (3) examine the chain of waste management, added value and  economic potential of waste in Bandung City. Data analysis used descriptive and value added methods. The results study showed that waste management refers to central and regional regulations. The issuance of Government Regulation Number 18 of 2016 and Regional Regulation of Bandung City Number 8 of 2016, change the authority of municipal sanitation from Sanitary Regional Company to Environmental and Sanitary Office (DLHK). DLHK assign the regional company due to limited resources in the period of transfer of authority. The company performance in 2015 had reached 83.8% (1,257 tons per day). Based on waste value chain, the distribution of added value equal relatively among economic actors. Economic potential of waste utilization can be used as an alternative funding source in waste handling, considering that so far the source of handling cost has come from levies, other revenue, and state budget subsidy.